Symptom burden and dysphagia associated with osteoradionecrosis in long-term oropharynx cancer survivors: A cohort analysis. (March 2017) - Wong, Angela T.T.; Lai, Stephen Y.; Gunn, G. Brandon; Beadle, Beth M.; Fuller, Clifton D.; Barrow, Martha P.; Hofstede, Theresa M.; Chambers, Mark S.; Sturgis, Erich M.; Mohamed, Abdallah Sherif Radwan; Lewin, Jan S.; Hutcheson, Katherine A.
Highlights: Retrospective study examined the relationship between mandibular ORN and chronic dysphagia. Patient population consisted of oropharynx cancer survivors treated with bilateral IMRT and systemic therapy. Prevalence of chronic dysphagia was higher in patients with ORN compared to those without. High-grade ORN was significantly associated with prevalence of dysphagia. Symptom burden was higher among patients with ORN, as measured using the MDASI-HN. Abstract: Objective: The purpose is to examine the relationship between mandibular osteoradionecrosis (ORN) and chronic dysphagia in long-term oropharynx cancer (OPC) survivors, and to determine the perceived symptom burden associated with ORN. Materials and methods: Medical records of 349 OPC patients treated with bilateral IMRT and systemic therapy were reviewed. ORN was graded using a published 4-point classification schema. Patients were considered to have chronic dysphagia if they had aspiration pneumonia, stricture or aspiration detected by fluoroscopy or endoscopy, and/or feeding tube dependence in long-term follow-up ⩾1 year following radiotherapy. MD Anderson Symptom Inventory – Head and Neck Module (MDASI-HN) scores were analyzed in a nested cross-sectional survey sample of 118 patients. Results: 34 (9.7%, 95% CI: 6.8–13.3%) patients developed ORN and 45 (12.9%, 95% CI: 9.6–16.9%) patients developed chronic dysphagia. Prevalence of chronic dysphagia was significantly higher in ORN cases (12/34, 35%) compared to those who did not develop ORN (33/315, 11%, p < 0.001). ORN grade was also significantly associated with prevalence of dysphagia (p < 0.001); the majority of patients with grade 4 ORN requiring major surgery (6 patients, 75%) were found to have chronic dysphagia. Summary MDASI-HN symptom scores did not significantly differ by ORN grade. Significantly higher symptom burden was reported, however, among ORN cases compared to those without ORN for MDASI-HN swallowing (p = 0.033), problems with teeth and/or gums (p = 0.016) and change in activity (p = 0.015) item scores. Conclusions: ORN is associated with excess burden of chronic dysphagia and higher symptom severity related to swallowing, dentition and activity limitations.